NILAI-NILAI PENDIDIKAN AGAMA ISLAM MULTIKULTURAL BERBASIS TASAWUF (STUDI FENOMENOLOGIS PADA SELOSOAN DI PESANTREN NGALAH) - Uswatun Chasanah (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2021)
The purpose of this study was to determine the values ​​of multicultural Islamic education based on Sufism which was developed in Selosoan. This type of research is descriptive-qualitative with a phenomenological approach that is used to understand the essence of a series of events involving the experience of people who actually experience the phenomenon. Data collection techniques through participatory observation, in-depth interviews, and document analysis. and data analysis using phenomenological analysis. While the values ​​of multicultural Islamic education are choices of human action that can be a guide in interacting with the social environment resulting from Islamic religious education that places multiculturalism as one of its visions that is egalitarian, inclusive, and humanist and remains firm on spiritual values. and based on the Qur'an and Al-Hadith. Meanwhile, Sufism is a science that studies efforts to get closer to Allah by practicing Islamic teachings in a kaffah way through Islam, faith, and ihsan. With the values ​​of multicultural Islamic religious education in Selosoan, it will benefit students comprehensively, not only in social life but also valuable in the sight of God because it is based on the purity and sanctity of intentions carried out solely because of Allah SWT.